Management Of Computer-Based Library (State-Owned Junior High School Semesta Semarang) - Ariati, Agustin (2012)
The objectives of this research are to describe (1) the room design characteristic of Computer-Based Library at Junior High School Semesta Semarang; (2) characteristic of Computer-Based Library Service at Junior High School Semesta Semarang; (3) characteristic of user satisfaction of Computer- Based Library at Junior High School Semesta Semarang. It is a qualitative research using ethnography design. It is conducted at Junior High School Semesta Semarang. The main subject of this study includes the Principal, librarian (library staff), and user at Junior High School Semesta Semarang. Data collection technique uses interview, observation, and documentation. Data analysis is started from (1) data collection, (2) data reduction, (3) data display, and (4) drawing conclusion. Data validity test uses credibility, transferability, conformability, and dependability. The result of this study includes (1) The room design of the Computerbased library at SMP Semesta Semarnag considers the user's comfort. The library of Junior High School Semesta Semarang is divided into three rooms, namely reading room, collection, and information access. Each room is equipped by digital facilities such as CCTV, internet connection, LCD, AC, and display board. (2) The library service of Junior High School Semesta Semarang includes circulation service, reference service, and information access service. The circulation service system uses Mixed access system, that is open access and close access as well as automation system. In the reference service, users can enjoy several literatures which are imported from Turkey and structured based on the type of the science. In the information access service, users can access information either about the reference from Semesta library or from other schools via digital library automatically. (3) The library users are satisfied on the service system that uses mixed access which is done digitally and automatically. The mixed access system facilitates user to find information. Uses do not need to pay anything in using library service, so they are more active to use the library. The ease and fast of finding information is good for the library user. The development of technology provided by the library such as automation system in circulation service, the availability of computer, database such as catalog and display board facilitate user to get quick information.